4. ETIKATERAPAN DALAM KAMPANVE PILKADA - E.P., Apriatni (FORUM, 2008)
Campaign is not an action that unplanned. It needs good preparation with various perspective considerations to get sympathy of electoral threshold in general election. It becomes ironic when campaign events emerge conflict that result in uncomfortable and public order annoyance. There are tree important aspects that relevant to campaign, they are awareness, attitude, and action. These three aspects interact each to others. The attention of party to ethics and morality interest sometime neglected, and prefer to the party interest that take a sides and even try to ruin politic rivals. It was aÂ  morality problem emerged on previous president election. The upcoming general election can be the right time to create strategy that can drive the community sympathy by paying attention to ethics and morality interest. Decisions to establish morality limits cannot be done individually, but it becomes the whole parties responsibility, competent that determine the regulation, organization, and individual relevant to local election as politician or voter. It aimed to reflect morality on local election events.